Integrated STEM – a step too far in primary education contexts?. Issue 4 (2nd October 2022) - Hourigan, M.; O'Dwyer, A.; Leavy, A. M.; Corry, E.
Abstract : The focus on integrated STEM (Science, Technology, Engineering, and Mathematics) education that prepares students for an ever-changing society is gaining momentum. Recent STEM education research has concentrated on developing guiding principles for integrating STEM amid the lack of a unified definition and varied implementations of STEM integration. Aware of the challenges posed by the inconsistent language and lack of consensus on a common definition, we recognise the importance of educators developing a shared conceptual framework and co-constructing a vision for STEM education. This research reports on the STEM education perspectives held by key stakeholders in Irish primary STEM education. Using qualitative surveys and interviews, we investigate primary teachers' and teacher educators' conceptions of STEM education alongside their perceptions of approaches to and the efficacy of integrated STEM education. Insights are provided into how engagement in STEM education professional development programmes supports the development of understandings and practices. The research contributes valuable insights into the unique perspectives of primary education practitioners regarding balancing the affordances of integrated STEM alongside the perceived threat to content knowledge development within the discrete STEM disciplines.